(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Multifarious cases about reading difficulties and deficiencies are typical problems that our country has been facing since then. In our government’s frustration to solve these problems, the Department of Education (DepEd) implemented a reading remediation program among schools. With that, researchers believe that studying the effectivity of the implemented program, it will be very helpful in discerning the results and impacts in addressing reading problems. The researcher utilized the Descriptive Method of research. In choosing the respondents who are teaching reading remediation program, purposive sampling techniques was used, selecting 20 Grade 1 teachers at San Bartolome Elementary School in Quezon City. The instruments used where survey questionnaires, observation, structured interviews, and focused group discussion. The majority of the respondents are female, 31-35 years old who are handling the reading remediation program with a different teaching position. The teacher-respondents more or less agree on the problems encountered in it. In the said program, teacher-respondents strongly agree on the solutions to problems encountered. Teacher respondents agree that it is effective for grade one pupil at San Bartolome Elementary School. This study may be utilized in crafting a guide to enhance it in terms of making possible solutions for the problems encountered during the implementation of the identified program. Teachers who are handling the Reading Remediation program should be an enthusiast in implementing the identified program and teachers should attend seminars related to the Reading remediation program. Also, teachers should be more resourceful, creative, and have initiative in implementing the program.